Financing sport post-COVID-19: using Modern Monetary Theory (MMT) to help make a case for economic recovery through spending on sport and recreation - Hammond, A. (Managing Sport and Leisure, 2020)
This commentary aims to explore the challenges of financing sport in light of the economic and health questions posed by the COVID-19 outbreak. Governments will have to spend large sums of public money to stimulate recovery; therefore, it is asked: how should sport and recreation spending be part of recovery plans? The case of the Montreal Olympics debt and deficit disaster is re-examined. It is argued that if the federal government (a currency issuer) underwrote the games many of the issues that followed may have been avoided. Therefore, this commentary challenges sport and leisure scholars to think about how sport and recreation could be part of the solution when fiscal policy is becoming the preferred antidote to the social and economic consequences of the Coronavirus pandemic.